Ancient environmental DNA reveals shifts in dominant mutualisms during the late Quaternary - Martin Zobel (Nature Portfolio, 2018)
Recently, an eDNA metabarcoding data set was used to describe northern high-latitude vegetation during the past 50,000 years. Here, Zobel et al. use the data set to examine how the abundance of key plant mutualistic traits changed during this period and discuss possible environmental drivers.